Development of Knowledge Management Based on Safety Audit for Design-Build Contract in High-Rise Building Projects - Arifuddin, R.; Latief, Y.; Wibowo, M. A.; Nugroho, D. B.; Latief, R. U.; Hamzah, S.; Mawarni, A. A. I.; Fadlillah, M. R. (Salehan Institute of Higher Education, 2026)
Audits play a crucial role in construction safety management systems (CSMS) by identifying discrepancies and evaluating the effectiveness of safety implementation. Despite Indonesia’s rapid infrastructure development, audit practices remain insufficient to prevent construction accidents. This research aims to formulate a conceptual framework for maturing a knowledge management-based CSMS audit to enhance the effectiveness of safety management implementation in construction projects. The study employed a quantitative approach using the least square method to test the significance of safety audit indicators, supported by descriptive analysis involving expert evaluations on three different construction projects. The findings revealed that the most influential safety audit elements are construction safety operations, followed by mastery and contribution to construction safety, safety planning, safety performance evaluation, and safety support. Expert assessments confirmed a high level of applicability of the proposed framework. The novelty of this study lies in the integration of knowledge management principles into the CSMS audit process, offering a more mature and structured approach to improving safety performance. This framework provides a practical tool to strengthen audit effectiveness and support continuous improvement in construction safety management within the Indonesian infrastructure sector.